Comparison of Complications of Harmonic Scalpel Versus Conventional Homeostasis in Patients Undergoing Near-Total Thyroidectomy at a Tertiary Care Hospital - Bilal Mehmood, Tariq Nwaz, Muhammat Atif Khan, Muhammad Umer Javaid, Aqsa Nadar, Sidra Manzoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare advantages and postoperative outcomes of harmonic scalpel versus conventional homeostasis in patients undergoing near-total thyroidectomy at a tertiary care hospital. Material and Methods: Total 34 patients were recruited in the study, and were equally distributed in two groups using blocked randomization. Operative time, post-operative fluid drainage, post-operative blood loss, mean hospital length, and occurrence of hypocalcemia were assessed in two groups. Results: In group A, mean operative time was 89.71±13.34 Mins while in group B it was 105±6.75 Mins, statistically significant difference was observed. In group A, post-operative blood loss observed was 61.47±8.27 ml, and in group B 74.47±12.80 ml (P < 0.05). The mean post-operative fluid drainage recorded in group A was 45.29±6.98 ml and in group B 69.06±10.83 ml (P < 0.05). In group A, mean hospital length was 2.18±0.72 days and in group B 3.41±1.12 days (P < 0.05). In group A, occurrence of hypocalcemia was 2 (11.8%) and in group B 3 (17.6%) (P > 0.05). Conclusion: In terms of operation duration, mean hospital stay, postoperative fluid drainage, and postoperative blood loss, harmonic thyroidectomy provides a secure and efficient substitute for traditional homeostasis. Keywords: Conventional Homeostasis, Postoperative Blood Loss, Harmonic Scalpel, Thyroidectomy